Exposure to Suicidal Behavior and Social Support Among Sexual- and Gender-Minority Youth - Mitchell, Kimberly J. (Pediatrics, 2021)
[Figure: see text] OBJECTIVES: In this study, we examine reports of exposure to suicidal behavior by youth sexual and gender identity. We explore how exposure is related to depressed mood in the context of high social support while accounting for cumulative adversity. METHODS: Data from a large national sample of youth aged 14 to 15 years in the United States (N = 3979) were collected online in 2018–2019. RESULTS: Sexual- and gender-minority youth were more likely to know someone close to them who attempted suicide, relative to cisgender heterosexual youth. Cisgender heterosexual youth were buffered from recent depressed mood when they endorsed having high social support in the context of exposure to suicidal behavior; less social support did not provide such a buffer. For cisgender sexual-minority male and female youth, exposure to suicidal behavior was related to recent depressed mood regardless of the level of social support. For gender-minority youth assigned female at birth, the combination of exposure and high social support was significantly associated with elevated depressed mood. Cumulative adversity accounted for some but not all of these relationships, indicating the influential role of exposure to suicidal behavior on depressed mood for some youth. CONCLUSIONS: These findings illustrate the complexities of social support and raise questions about its potential to magnify stress rather than serve as a buffer for some youth. Although findings need to be replicated, suicide prevention efforts should carefully consider how to promote resilience among these suicide-exposed sexual- and gender-minority youth who may themselves be at risk for suicidal ideation and behavior.